The Role of Local Culture Learning in Character Forming of Ibtidaiyah Madrasah Students (MI) - Rahimul Harahap (Budapest International Research and Critics University, 2022)
This paper was made by the author aiming to describe the role of local wisdom in shaping the character of elementary school-aged children in the era of globalization. Progress in all fields in this era of globalization causes both positive and negative impacts. The research carried out by the author uses a qualitative descriptive method that describes events as they occur. The results of the research that has been carried out are that the role of local wisdom is quite large as the formation of the character of students, because the character of children is formed based on the habits they often do, apart from parents environmental and cultural factors are also influential in it.